HUBUNGAN ANTARA KADAR HEMOGLOBIN DAN STATUS GIZI DENGAN GANGGUAN SIKLUS MENSTRUASI PADA SISWI - Carolin, Bunga Tiara; Novelia, Shinta; Fatiha, Salysia Manif (STIKES Abdurahman. Pusat Informasi dan Manajemen, 2025)
Background: Menstrual disorders often occur in adolescents, in the world the prevalence of menstrual cycle disorders in early adolescent women is around 45%, menstrual disorders can be serious. can be a sign of no ovulation, heavy bleeding and occurs over a long period of time can cause anemia in adolescents factors related to menstrual cycle disorders include stress, nutritional status, hemoglobin levels, physical activity, and sleep duration. Purpose: This study aims to determine the relationship between hemoglobin levels and nutritional status with menstrual cycle disorders in SMK students. Methodology: This study is a quantitative research that is correlational, the method used is non-experimental with cross sectional. The sample in this study amounted to 70 respondents, female adolescent students in grades X-XII. The sampling technique used purposive sampling technique, using the Chi square test. Research Results: Univariate results showed that the majority of respondents did not experience menstrual cycle disorders 57.1%, the majority of normal hemoglobin levels 70% and the majority of normal nutritional status (58,6%. Bivariate results show a relationship between hemoglobin levels (p-value = 0.018) and nutritional status (p-value = 0.004) with menstrual cycle disorders. Conclusion: there is a relationship between hemoglobin levels and nutritional status with menstrual cycle disorders in female students of SMK. Suggestion: Young women need to consume iron supplements regularly and their nutritional status should remain in the normal category, namely by maintaining a healthy diet, exercising regularly so that their nutritional status is normal and their hemoglobin levels are normal and not anemic.